Desain Sistem Knowledge Management Berbasis Kolaborasi untuk Meningkatkan Berbagi Pengetahuan Guru SMA melalui Integrasi Google Classroom - Fajar Muttaqi; Moh Alfaujianto; Nurul Badriah (Informatics Study Program, Faculty of Engineering and Computers, Baturaja University, 2025)
Knowledge sharing activities among high school teachers still face several challenges, such as the lack of collaborative platforms, undocumented knowledge, and insufficient technological support aligned with their daily teaching practices. This study aims to design a collaborative-based Knowledge Management System (KMS) that enhances knowledge sharing among teachers by integrating with a widely used learning platform, namely Google Classroom. The research uses a system design approach consisting of user needs analysis, functional design (use case diagram), and user interface visualization (wireframe UI). The result is a system design featuring four main components: knowledge uploading, discussion forums, content repository, and interactive dashboard—all integrated with teachers’ Google accounts. The system is designed to be user-friendly, contextually relevant, and to strengthen the culture of collaboration in knowledge management. Expert validation indicates that the design is feasible for further development, with recommendations to improve content moderation and user contribution management. This study concludes that a collaborative KMS integrated with Google Classroom holds strong potential as an innovative solution to strengthen the teacher knowledge ecosystem in secondary schools. Further implementation and pilot testing are recommended for future research stages.